Tren Pemahaman al-Qur’an Masyarakat Indonesia: Sebuah Tinjauan Literatur Sistematis dari 2019 hingga 2024 - Riza, Zikri (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2025)
The study of the living quran appears as a relatively new area of quranic studies which has not been found yet in classical and medieval Islamic intellectualism tradition. Indonesian Muslim Scholars articulated their interests in that discourse over various scholarly research. To grasp the trends of Indonesian understanding of the Quran, I was encouraged to delve academic writings published whose main focus is the living quran in Indonesian context. This work imposes systematic literature review (SLR) method with previously formulated scientific procedures. The result reveals that the community has embodied the sacred text in various medium showing the diversity of social entity types enlivening the Quran. The preliminary factors behind the form of the Quran’s practices are varied either, depending on man’s intention to internalize the divine message. From a methodological aspect, studies whose objects are living quran in society entail scientific set intensification due to the limitation of the research methods applied by scholars.